Implikasi Hukum dari Tindak Kejahatan Anak di Bawah Umur: Analisis Kasus Bullying di Pondok Pesantren Al-Hanafiyah Kediri - Sachmaso, Hana Humaira; Harsanti, Khairunnisa Putri; Izzati, Aulia Putri; Fawwaz, Razky; Prasetyo, Handoyo (Media Hukum Indonesia (MHI), 2024)
Bullying is defined as the abuse of power by an individual or group against a weaker party, which causes physical, psychological or social suffering to the victim. Based on Law Number 35 of 2014, bullying against children is a criminal act with heavy legal sanctions. A case study of students in Kediri who died as a result of abuse at the Islamic boarding school shows the serious impact of bullying. This research uses normative juridical methods to analyze regulations and legal protection for victims of bullying, as well as legal implications for perpetrators who are still minors. The findings show that lack of supervision and wrong parenting patterns contribute to the high number of bullying cases in Islamic boarding schools. To prevent similar incidents, a restorative justice approach and collaboration between the government, schools and the community is needed to protect children from violence.